The Effect of Season-Long Temperature Increases on Rice Cultivars Grown in the Central and Southern Regions of China - Yang, Zhiyuan; Zhang, Zuolin; Zhang, Tong; Fahad, Shah; Cui, Kehui; Nie, Lixiao; Peng, Shaobing; Huang, Jianliang (Frontiers in Plant Science, 2017)
Rice production is challenged by the asymmetric increases in day and night temperatures. Efforts are required to improve our understanding of the impact of climate change on rice production. To this end, a two-year experiment was conducted to evaluate the response of mid-season rice growth in the central and southern regions of China to elevated temperatures. Four replicates of four widely planted indica rice cultivars (Huanghuazhan: HHZ; Shanyou63: SY63; Yangliangyou6: YLY6; Liangyoupeijiu: LYPJ) were subjected to four elevated-temperature treatments (control: ambient temperature; NW: night-time warming; DW: daytime warming; AW: all-day warming) generated by an open-top hot-blast system under field conditions. This apparatus causes an approximate 2℃ increase in the rice canopy temperature. Of all the elevated-temperature treatments, AW was the most devastating treatment for all rice cultivars, negatively affecting nearly all of investigated parameters, including grain yield and its components, dry matter accumulation, biomass, and harvest index (HI). The AW treatment decreased the grain yield by 11-35% and 43-78% in 2015 and 2016, respectively. No significant reduction in the grain yield was observed in the DW and NW treatments in 2015. However, the grain yield was decreased in DW and NW treatments by 20%-52% and 18%-55%, respectively, in 2016. Furthermore, the temperature-driven degradation of pollen viability, the number of pollen grains adhering to the stigma and pollen germination on the stigma caused spikelet sterility and thereby decreased the grain yield. The YLY6 and SY63 cultivars performed better than the HHZ and LYPJ cultivars with respect to grain yield and its components in all elevated-temperature treatments in both years. However, 42.97% and 61.01% reductions still occurred for the SY63 and YLY6 cultivars, respectively, in the AW treatment in 2016. The above results suggested that the elevated temperature may cause a noteworthy reduction in the productions of these widely planted genotypes in central and southern regions of China. To ensure the security of rice production in this region in an expected global warming environment, currently planted varieties will need to be replaced by heat-resistant varieties in the future.